M=((3)/(4)-(3)/(5)+(3)/(7)+(3)/(11))/((13)/(4)-(13)/(5)+(13)/(7)+(13)/(11))
Giải giùm mình nhé
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
-3/11.(-22)/66.121/15
=(-3).(-22).121
11.66.15
=11
15
3/7.2/5.7/3.20.19/72
=3.2.7.20.19
7.5.3.72
=76
16
6/7.8/13+6/13.9/7-3/13.6/7
=6/7.8/13+6/7.9/13-3/13.6/7
=6/7.(8/13+9/13-3/13)
=6/7.14/13
=12/13
-1/4.152/11+68/4.(-1)/11
=152/4.(-1)/11+68/4.(-1)/11
=(-1)/11.(152/4+68/4)
=(-1)/11.220/4
=-110/22
-5/7.2/11+(-5)/7.9/11+12/7
=-5/7.2/11+-5/7.9/11+12/7
=-5/7.(2/11+9/11)+12/7
=-5/7.1+12/7
=(-5)/7+12/7
=7/7
=1
146/13-(18/7+68/13)
=146/13-18/7-68/13
=(146/13-68/13)-18/7
=78/13-18/7
=6-18/7
=42/7-18/7
=24/7
\(\frac{\frac{3}{4}-\frac{3}{5}+\frac{3}{7}+\frac{3}{11}}{\frac{13}{4}-\frac{13}{5}+\frac{13}{7}+\frac{13}{11}}=\frac{3\left(\frac{1}{4}-\frac{1}{5}+\frac{1}{7}+\frac{1}{11}\right)}{13\left(\frac{1}{4}-\frac{1}{5}+\frac{1}{7}+\frac{1}{11}\right)}=\frac{3}{13}\)
\(\frac{\frac{3}{4}-\frac{3}{5}+\frac{3}{7}+\frac{3}{11}}{\frac{13}{4}-\frac{13}{5}+\frac{13}{7}+\frac{13}{11}}\\ =\frac{3\left(\frac{1}{4}-\frac{1}{5}+\frac{1}{7}+\frac{1}{11}\right)}{13\left(\frac{1}{4}-\frac{1}{5}+\frac{1}{7}+\frac{1}{11}\right)}\\ =\frac{3}{13}\)
5) Ta có: \(\dfrac{\left(5\sqrt{3}+\sqrt{50}\right)\left(5-\sqrt{24}\right)}{\sqrt{75}-5\sqrt{2}}\)
\(=\dfrac{5\left(\sqrt{3}+\sqrt{2}\right)\left(\sqrt{3}-\sqrt{2}\right)^2}{5\left(\sqrt{3}-\sqrt{2}\right)}\)
=1
a) \(\frac{1}{3}-\frac{3}{4}-\left(\frac{-3}{5}\right)+\frac{1}{64}-\frac{2}{9}-\frac{1}{36}+\frac{1}{15}\)
=\(\left(\frac{1}{3}+\frac{3}{5}+\frac{1}{15}\right)-\left(\frac{3}{4}+\frac{2}{9}+\frac{1}{36}\right)+\frac{1}{64} \)
=\(\frac{5+9+1}{15}-\frac{27+8+1}{36}+\frac{1}{64}\)
= \(1+1+\frac{1}{64}=2\frac{1}{64}\)
a: =-5/9-4/9+8/15+7/15-2/11=-2/11
b: =10/17+7/17-5/13-8/13+11/25
=11/25
c: =(9/12-2/12)*3/2=7/12*3/2=21/24=7/8
d: =(31/10-25/10)*3-2
=3/5*3-2
=9/5-2
=-1/5
A = 4/1.3 + 4/3.5 + 4/5.7 + ... + 4/11.13
A = 2.(2/1.3 + 2/3.5 + 2/5.7 + ... + 2/11.13)
A = 2.(1 - 1/3 + 1/3 - 1/5 + 1/5 - 1/7 + ... + 1/11 - 1/13)
A = 2.(1 - 1/13)
A = 2.12/13
A = 24/13
M = ( 3/4 - 3/5 + 3/7 + 3/11 )/( 13/4 - 13/5 + 13/7 + 13/11)
M = 3.( 1/4 - 1/5 + 1/7 + 1/11)/13. ( 1/4 - 1/5 + 1/7 + 1/9 )
M = 3/13